PERAN KADER PKK DALAM PERSIAPAN KEHAMILAN DITINJAU DARI ASPEK FISIK DAN PSIKOLOGI - Januar Dwi Christy; Indrianita, Vivin Indrianita (Rena Cipta Mandiri, 2025)
PKK cadres play an important role in supporting prospective brides (catin) and women of reproductive age (WRA) in preparing for pregnancy through health education. This study aims to assess the level of understanding of PKK cadres regarding pregnancy preparation before and after health counseling. The research employed a quasi-experimental design (pretest-posttest) involving 50 PKK cadres in Tenggulunan Village, Sidoarjo. The study design used a quasi-experimental method with a pre-test and post-test design. The results showed that the cadres' knowledge significantly increased from 30% (low category) to 90% (good category) after three counseling sessions (p<0.05). Counseling was effective in improving PKK cadres' understanding of pregnancy preparation. Similar programs could be integrated into regular PKK activities.